FUNGSI PEMERINTAHAN TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT TERDAMPAK COVID 19 DI DESA TIMORENG PANUA - Siti Nurhalisa; Muhammad Rohady Ramadhan; Andi Dwi Resqi Pramana; Andi Riska Andreani S; Damayanti Trisnasari (PRAJA: Jurnal Ilmiah Pemerintahan, 2022)
The purpose of the study was to determine the implementation of government functions in Timoreng Panua Village, Sidenreng Rappang Regency and to determine the function of government to improve the welfare of the people affected by COVID-19 in Timoreng Panua Village. The population of this study amounted to 146 people, while the research sample used a total random sampling of 73 people. Data collection techniques in this study used the techniques of Observation, Interview, Literature Study and Questionnaire. The research method uses descriptive qualitative. The data were then analyzed using frequency and percentage tables. The results of this study indicate that the implementation of government functions in Timoreng Panua Village, Sidenreng Rappang Regency is considered quite good with an average percentage of 74.12%. The function of government to improve the welfare of the people affected by COVID-19 in Timoreng Panua Village is considered quite good with an average percentage result, which is 82.02%. The results of simple linear regression showed that there was a significant effect of variable X on government functions on variable Y, increasing people's welfare by 86%.